DISFUNGSI LEMBAGA PENGELOLAH ZAKAT DALAM MENGENTASKAN KEMISKINAN DI KOTA PALOPO - Beddu, Rahmawati; Abdain, Abdain (Maddika : Journal of Islamic Family Law, 2017)
This journal discusses "Why is there a dysfunction of zakat management institutions against poverty alleviation in Palopo City? From these problems arise several questions: 1) How the system of zakat management in Palopo city? 2) What factors affect the dysfunction of zakat management institutions in alleviating poverty? 3) How to overcome the dysfunction of zakat management institutions against poverty alleviation?The results showed that the collection of zakat fitrah funds and distribution is given responsibility to the UPZ in each mosque while the zakat mal reporting is still submitted to BAZNAS Palopo City. In addition, fundraising is also entrusted to SKPD (Zakat collector whose position in the staffing section) collects zakat through the treasurer and the treasurer submits it to the bank, either Bank BPD Sul-Sel-Bar, BSM and other Sharia banks. Factors affecting disfunction of Zakat Institution is 1. Funding system is not optimal yet, so the existing zakat funds with poor Muslim citizens have not been balanced, 2. There is a tendency of poverty rate to increase because citizens pretend to feel poor, 3.Some Muslims in  Palopo have not realized and do not understand that the charity is a duty for Muslims to be issued so that the lack of zakat funds that cause zakat management institutions have not been maximized in an effort to alleviate poverty through the existing zakat funds. While How to overcome the dysfunction of zakat management institutions against poverty alleviation is Community leaders provide guidance and knowledge to the public about the importance, benefits and laws of zakat, the Government supports the management of zakat with clear and firm regulations. For those who are reluctant to issue their zakat will be subject to the appropriate sanctions, the community supports the institution of zakat by channeling funds to the institution. as well as zakat amil develop the nature of trust in manage zakat and distribute zakat appropriately eight asnaf